Analysis of Factors Influencing Students' Learning Success Rate in National Examinations - Hasanah, Uswatun (Jurnal Ar Ro'is Mandalika (Armada), 2023)
The National Examination (UN) is a crucial assessment tool in many educational systems worldwide, determining students' academic achievements and educational progress. This study aims to analyze the factors influencing students' success rates in the National Examination. Utilizing a qualitative approach and conducting a comprehensive review of existing literature through library research, this study investigates various factors that impact students' performance in the National Examination. The analysis includes factors such as socio-economic background, access to educational resources, teaching quality, study habits, and psychological factors like motivation and self-efficacy. The findings reveal that socio- economic status significantly influences students' preparation and performance in the National Examination. Moreover, access to educational resources and quality teaching positively correlate with students' success rates. Additionally, students' study habits, including time management, self-discipline, and effective learning strategies, play a vital role in determining their performance in the examination. Furthermore, psychological factors such as motivation, self-confidence, and perceived academic competence contribute significantly to students' success in the National Examination. By understanding these factors, educators and policymakers can develop targeted interventions and strategies to improve students' preparation and performance in the National Examination, thereby enhancing overall educational outcomes and promoting equity in education.